A Longitudinal Study on Deforestation Trends in Indonesia from 1996 to 2022 - Khoiriyanah, Umi; Oktavilia, Shanty (LifeSciFi, 2025)
This study aims to analyse spanning 1996–2022, analyzed deforestation determinants in Indonesia using a Vector Error Correction Model (VECM) to assess short and long-term variable relationships. We focused on GDP per capita, Foreign Direct Investment (FDI), population density, and renewable energy consumption. Results support the Environmental Kuznets Curve (EKC) hypothesis, showing an inverted U-shaped relationship between GDP per capita and deforestation. Deforestation initially increased with economic growth but declined after a turning point of USD 2,443.41 million GDP per capita, around 2009–2010. This suggests that as Indonesia developed, environmental awareness and forest conservation efforts increased. Furthermore, population density and renewable energy consumption significantly reduced deforestation, While FDI had an insignificant positive effect, its impact was statistically irrelevant when considering overall market trends. Policy implications highlight the need for stronger forest governance post-economic development era, to ensure sustainable management, combat illegal activities, and mitigate environmental degradation and have turning point, strict regulation of land-based renewable energy projects, and careful monitoring of investments potentially threatening forest sustainability.